2020
DOI: 10.1590/1678-9199-jvatitd-2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and cytotoxic effect of the skin secretion from the red-spotted Argentina frog Argenteohyla siemersi (Anura: Hylidae)

Abstract: Background: Argenteohyla siemersi (red-spotted Argentina frog) is a casque-headed tree frog species belonging to the Hylidae family. This species has a complex combination of anti-predator defense mechanisms that include a highly lethal skin secretion. However, biochemical composition and biological effects of this secretion have not yet been studied. Methods: The A. siemersi skin secretion samples were analyzed by mass spectrometry and chromatographic analysis (MALDI-TOF/MS, RP-HPLC and GC-MS). Proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The parotoid gland secretion of the R. marina toad has seven protein bands 9 . Argenteohyla siemersi frog skin secretions had six protein bands 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parotoid gland secretion of the R. marina toad has seven protein bands 9 . Argenteohyla siemersi frog skin secretions had six protein bands 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Fusco et al 10 reported that the secretion of the skin frog Argenteohyla siemersi showed six protein band patterns with molecular weights ranging from 15-55 kDa. Based on existing research on several Amphibian species, it can be estimated that there are variations in the protein band patterns on the skin secretions of C. parvaccola and C. rufipes, which are part of the C. chalconota species complex.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes presenting such activities have already been described as important toxins for snake venoms [81,82] and were also described in some amphibians from different genus, for example phospholipase in Pithecopus azureus [83] and serine peptidases in Duttaphrynus melanostictus [84]. Furthermore, Fusco et al 2020 [85] studied the epidermal secretion of Argenteohyla siemersi and described both phospholipasic and hemolytic activities. They also reported that that venom is cytotoxic and capable of promoting necrosis which is independent of the proteolytic activity, a different activity pattern from C. greeningi (included in the same genus).…”
Section: Amphibianmentioning
confidence: 98%